Parental expectations and prosocial behavior of adolescents from low-income backgrounds. A cross-cultural comparison between three countries: Argentina, Colombia and Spain - Mesurado, Maria Belen (2014)
Parental expectations are influenced by cultural models, which in turn are subject to a great influence from historically fluctuating features of the socioeconomic background. Parental expectations seem to be linked to children’s social and emotional development in terms of empathy and prosocial behavior. The current study aims to (a) compare low-income adolescents’ perceptions of parental expectations of prosocial and antisocial behavior across three Latin countries (Argentina, Colombia, and Spain), (b) compare the empathy and prosocial behavior between the three countries, (c) compare the prosocial behavior between the three countries, and (d) study the effect of perceived parental expectations and empathy on the prosocial behavior of adolescents in all three of the countries studied in this research. The sample was made up of 446 Argentinean adolescents, 474 Colombian adolescents, and 632 Spanish adolescents. The Expected Parental Reactions Scale, Interpersonal Reactivity Index, and Prosocial Behavior Questionnaire were used to measure the variables included in this study. Results reveal considerable differences between children’s perceptions of parental expectations in different countries. Results also show the existence of significant differences between male and female adolescents. In all three countries, girls score more highly than boys in prosocial behavior and empathy. Furthermore, we find that low-income Argentinean adolescents score more highly than Spanish and Colombian adolescents in prosocial behavior measures. Finally, expected parental reactions toward prosocial behavior and empathy seem to have an influence on the adolescents’ development of prosocial behavior in all three countries.